A STUDY ON SOURCES, MANAGEMENT AND REPLACEMENT OF POTATO (SOLANUM TUBEROSUM L.) SEED IN WESTERN UTTAR PRADESH - Kharumnuid, Pynbianglang (Potato Journal, 2022)
Presently in India, the actual potato yield is far below the potential yield. Enhancing the seed replacement rateis one of the important strategies to narrow the gap between the actual and potential yields. Hence, the present study wasconducted to examine the sources, replacement rate and management of potato seed and constraints for availing quality seedin Western Uttar Pradesh. The primary data was collected from 85 randomly selected farmers of Bulandshahar and Meerutdistricts. The study revealed that the Kufri Bahar, Kufri Pukhraj and Kufri Khyati were the major potato varieties. Localvarieties were still prevalent among farmers. The major seed sources were farm saved seeds, fellow farmers and formalsources like department of agriculture, SAUs and research institutes. Farmers have good knowledge of seed managementactivities like maintenance of spacing, seed rate, seed retention period and followed them properly. The overall seedreplacement rate for certified seed was around 39 percent. There was a direct relationship between seed replacement rateand farm size. The overall seed replacement rate of seed of improved potato varieties was about 92 percent. The identifiedconstraints were high cost of quality seed, poor quality of seed, lack of proper storage and transportation facilities, lack ofseed of required varieties and lack of information about improved varieties. The study suggested that extension strategiesand institutional mechanisms should be formulated for popularization of the new varieties and reliable seed sources andfor regular supply of certified and quality seeds to all categories of farmers to enhance the seed replacement rate.